The impact of large animal extinctions on nutrient fluxes in early river valley civilizations. Issue 12 (30th December 2013) - Doughty, Christopher E.; Wolf, Adam; Malhi, Yadvinder
Abstract : Urbanization began independently in four river valley civilizations ∼3, 500–5, 000 years before the present (ybp) in fertile river valleys that originally had free‐ranging large animals, including elephants, that eventually went locally extinct. Such large animals are disproportionally important in the lateral spread of nutrients away from nutrient concentration gradients common near floodplains, and the local extinction of the animals would have reduced this flow of nutrients into surrounding regions. Prior to the use of manure as a fertilizer, this natural spread of nutrients would have increased productivity and food yield, and its absence would have immediately decreased fertility to regions outside the floodplains. Here we calculate this changing nutrient flux using a "random walk" model and estimate that phosphorus (P) concentrations in the vegetation were reduced by >40% outside the floodplain following the loss of these animals and the process could take between 840 and 6, 800 years depending on the region and the model parameters used. In the short term, we hypothesize that the decreased fertility may have reduced food yields and driven early agriculturalists from the outer regions away from rivers towards the more fertile floodplains. In the long term, yield and populations in outer regions would have decreased, constraining the potential growth of these civilizations, thus demonstrating how the loss of a key ecosystem service could have important repercussions for humanity that continue over thousands of years.